DESIGN OF A LEARNING MANAGEMENT SYSTEM WITH LEARNING AIDS SUITABLE FOR VISION IMPAIRED UNIVERSITY STUDENTS - Rodrigo, S. (My University, 2012)
Every individual, irrespective of race, gender, nationality, ethnic or social origin, religion or political preference, age or disability has an equal right for education. Vision impaired students are no exception. In this Information Age, use of computers as assistive technology in education has become vital. Even though this is true for the developed world, In the Sri Lankan context most of the vision impaired students are not in a position to use Information Technology for their educational purposes due to many reasons. This study focuses mainly on the process of developing a Learning Management System (LMS) for vision impaired university students in order to enhance their quality of education. This study focuses on How a Learning Management System with Digital Accessible Information System (DAISY) technology, Sinhala Digital Talking Books and a Sinhala Text to Speech Convertor can be developed to facilitate the teaching and learning problems of vision impaired university students. Finally developing a Framework that can be used as a guide to develop such advanced LMSs for vision impaired university students is presented. The main objective of this study is to develop a framework to guide the designing of Learning Management Systems for Vision impaired students. First the researcher designed a model based on 3 stages, Firstly the objectives of a Learning Management System, secondly qualitative characteristics of the Learning Management System for vision impaired students and components of the Learning Management System for vision impaired students. Based on these 3 stages the researcher identified 32 characteristics and grouped these into 3 categories (System Design, Content Design and Service Design). The overall success of vi Learning Management Systems initiatives depends on the attainment of success at each of these stages of Learning Management Systems development. This research study attempts, what is trying to be done is to underline the importance of each aspect of a Learning Management System which directly effects the overall success and learner's satisfaction. The developed Framework can be used as a guide in developing such advanced LMSs for vision impaired university students.